MicroRNA expression levels in the nucleus accumbens correlate with morphine‐taking but not morphine‐seeking behaviour in male rats. (29th March 2022) - Gillespie, Aria; Mayberry, Hannah L.; Wimmer, Mathieu E.; Sillivan, Stephanie E.
Abstract: A powerful motivation to seek opioids remains after drug cessation and intensifies during extended periods of abstinence. Unfortunately, biomarkers associated with continued drug seeking have not been described. Moreover, previous studies have focused on the effects of early abstinence with little exploration into the long‐term drug‐induced mechanisms that occur after extended abstinence. Here we demonstrated that 30 days (D) of forced abstinence results in a time‐dependent increase in morphine seeking in a rat model of morphine self‐administration (SA). We measured expression of known drug‐responsive microRNAs (miRNAs) in the nucleus accumbens, an area critical for reward‐related plasticity, during early or late abstinence in animals that underwent either a cue‐induced relapse test or no relapse test. miRNAs are small noncoding RNAs that represent suitable biomarker candidates due to their long‐lasting nature. mir‐32‐5p levels during early abstinence negatively correlated with active lever pressing in both cue‐exposed and cue‐naïve animals. mir‐1298‐5p positively correlated with drug SA history after a relapse test during late abstinence. When animals underwent acute abstinence with no relapse test, mir‐1298‐5p correlated with drug infusions and active lever pressing during SA. In late abstinence with no relapse test, mir‐137‐3p negatively correlated with drug infusions. Regulation of mir‐32‐5p target genes and significant correlation of target gene mRNA with mir‐32‐5p was observed after abstinence. These results indicate that lasting regulation of miRNA expression is associated with drug intake following morphine SA. In addition, we conclude that the miRNA profile undergoes regulation from early to late abstinence and miRNA expression may indicate past drug history.